2022
DOI: 10.18632/aging.203893
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effects of icariin on ageing, various neurological, neuropsychiatric disorders, and brain injury induced by radiation exposure

Abstract: Epimedium brevicornum Maxim, a Traditional Chinese Medicine, has been used for the treatment of impotence, sinew and bone disorders, "painful impediment caused by wind-dampness," numbness, spasms, hypertension, coronary heart disease, menopausal syndrome, bronchitis, and neurasthenia for many years in China. Recent animal experimental studies indicate that icariin, a major bioactive component of epimedium may effectively treat Alzheimer's disease, cerebral ischemia, depression, Parkinson's disease, multiple sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 207 publications
0
15
0
Order By: Relevance
“…We first demonstrated that ICA significantly improved cognitive function and autonomous behavior, reduced neuronal damage, and reversed the protein levels and activities of glycolytic key enzymes, and expression of protein molecules of the canonical Wnt signaling pathway, in 3 9 Tg-AD mice back to wild-type levels. Next, we further found that ICA increased cell viability and effectively improved the dysfunctional glycolysis in HT22 cells injured by Ab [25][26][27][28][29][30][31][32][33][34][35] . However, when canonical Wnt signaling was inhibited by DKK1, the above effects of ICA on glycolysis were abolished.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…We first demonstrated that ICA significantly improved cognitive function and autonomous behavior, reduced neuronal damage, and reversed the protein levels and activities of glycolytic key enzymes, and expression of protein molecules of the canonical Wnt signaling pathway, in 3 9 Tg-AD mice back to wild-type levels. Next, we further found that ICA increased cell viability and effectively improved the dysfunctional glycolysis in HT22 cells injured by Ab [25][26][27][28][29][30][31][32][33][34][35] . However, when canonical Wnt signaling was inhibited by DKK1, the above effects of ICA on glycolysis were abolished.…”
mentioning
confidence: 75%
“…For thousands of years, Epimedium has been employed as a traditional Chinese herbal medicine [28]. It possesses a host of pharmacological effects, including antitumor [29], anti-aging [30,31], anti-oxidant and antiinflammatory activities [32,33], and regulation of glucose metabolism [34]. Importantly, it is reported that ICA can cross the blood-brain barrier [35], and its protective effects in the neurons have been reported continuously in multiple models of AD [30,[36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Icariin (ICA) is the main active component of flavonoids in the Herba Epimedii that has a wide range of pharmacological effects, including anti-inflammatory ( Luo et al, 2022 ), antioxidant ( Li et al, 2022 ), antidepressant ( Xu et al, 2020 ), etc. In addition, ICA was found to improve fur status and increase body weight, sucrose preference, and activity time in the forced swimming test in depressed rats induced by CUMS.…”
Section: Transcription Factorsmentioning
confidence: 99%
“…ICA can inhibit the hyperphosphorylation of tau by inhibiting the PI3K/Akt-dependent GSK-3β signaling pathway, thereby exerting neuroprotective effects on Aβ25-35-treated PC12 cells ( Zeng et al, 2010 ). The improvement effect of ICA on learning and memory was observed in a permanent bilateral common carotid artery ligation (2-VO) rat model, an aluminum-induced AD rat model, and an APP/PS1Tg mouse model ( Li L. R. et al, 2022 ).…”
Section: Single Tcms and Their Active Ingredientsmentioning
confidence: 99%